Can Short-Term Ocular Dominance Plasticity Provide a General Index to Visual Plasticity to Personalize Treatment in Amblyopia? - Tao, Chunwen; He, Zhifen; Chen, Yiya; Zhou, Jiawei; Hess, Robert F. (Frontiers in Neuroscience, 2020)
Purpose: Recently, Lunghi et al showed that amblyopic eye’s visual acuity per se after 2 months of occlusion therapy could be predicted by a homeostatic plasticity, i.e., the temporary shift of perceptual eye dominance observed after a 2-hour monocular deprivation, in children with anisometropic amblyopia(Lunghi et al., 2016). In this study, we assess whether the visual acuity improvement of the amblyopic eye measured after 2 months of occlusion therapy could be predicted by this plasticity. Methods: Seven children (6.86 ± 1.46 years old; SD) with anisometropic amblyopia participated in this study. All patients were newly diagnosed and had no treatment history before participating our study. They finished 2 months of refractive adaptation and then received a 4-hour daily fellow eye patching therapy with an opaque patch for a 2-month period. Best-corrected visual acuity of the amblyopic eye was measured before and after the patching therapy. The homeostatic plasticity was assessed by measuring the temporary shift of perceptual eye dominance from 2-hour occlusion of the amblyopic eye before treatment. A binocular phase combination paradigm was used for this study. Results: We found that there was no significant correlation between the temporary shift of perceptual eye dominance observed after 2-hour occlusion of the amblyopic eye and the improvement in visual acuity in the amblyopic eye from 2-hour of classical patching therapy. This result, although in disagreements with the conclusions of Lunghi et al involving the short-term patching of the amblyopic eye, is in fact consistent with a reanalysis of Lunghi et al’ s data. Conclusions: The short-term changes in perceptual eye dominance as a result of short-term monocular deprivation do not provide an index of cortical plasticity in the general sense such that they are able to predict acuity outcomes from longer term classical patching.